Integration of Cash Waqf in The Halal Value Chain Ecosystem: A Strategy to Strengthen The Competitiveness of Halal Products - Izzun Khoirun Nissa; Yuni Safitri; Baidar Mohammed Mohammed Hasan (haria Economics Study Program, Faculty of Islamic Economics and Business, UIN Sunan Gunung Djati Bandung, 2025)
Non Indexed Publication (Tier 4)